2016
DOI: 10.1038/ncomms11287
|View full text |Cite
|
Sign up to set email alerts
|

Structural control of mixed ionic and electronic transport in conducting polymers

Abstract: Poly(3,4-ethylenedioxythiophene) doped with poly(styrenesulfonate), PEDOT:PSS, has been utilized for over two decades as a stable, solution-processable hole conductor. While its hole transport properties have been the subject of intense investigation, recent work has turned to PEDOT:PSS as a mixed ionic/electronic conductor in applications including bioelectronics, energy storage and management, and soft robotics. Conducting polymers can efficiently transport both holes and ions when sufficiently hydrated, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
843
2
15

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 738 publications
(892 citation statements)
references
References 53 publications
32
843
2
15
Order By: Relevance
“…For example, PEDOT:PSS polymer blend contains two polymers: PEDOT, which can be electrically conductive, and PSS, which conducts only ions. It has been shown that PEDOT:PSS is a two phase system consisting of PEDOT-rich and PSS-rich grains [44]. The PSS-rich grains are amorphous while PEDOT-rich grains form the crystalline lamellae regions with typical thickness on the order of 10-30 nm.…”
Section: Charge Transport Models For Conductive Polymersmentioning
confidence: 99%
“…For example, PEDOT:PSS polymer blend contains two polymers: PEDOT, which can be electrically conductive, and PSS, which conducts only ions. It has been shown that PEDOT:PSS is a two phase system consisting of PEDOT-rich and PSS-rich grains [44]. The PSS-rich grains are amorphous while PEDOT-rich grains form the crystalline lamellae regions with typical thickness on the order of 10-30 nm.…”
Section: Charge Transport Models For Conductive Polymersmentioning
confidence: 99%
“…During ES, charges on the metallic collection plate move instantaneously given the time scales associated with fiber deposition. Motion associated with charge in the polymer (much slower than motion of charge in metals) is dictated by ionic mobility of the polymer [256]. Resultant fiber diameter depends largely on the flow rate, applied voltage, and fluid surface tension of the melted polymer [257,258].…”
Section: Es Fabrication Of Organic Micro-and Nano-fiber Devicesmentioning
confidence: 99%
“…Without modification, PEDOT:PSS films exhibit a relatively low conductivity of 0.1–1 S cm −1 because of the large excess of inactive PSS − inhibiting charge transport between PEDOT + crystallites. The conductivity of PEDOT:PSS has been enhanced by orders of magnitude to well over 1000 S cm −1 through the incorporation of co‐solvents or by post treatments with strong acids 42, 43, 44, 45. This enhancement is attributed to a higher degree of ordering and increased domain purity of the PEDOT + crystallites combined with a partial removal of excess PSS − .…”
Section: Introductionmentioning
confidence: 99%